SHIGA, TOXIN-PRODUCING ESCHERICHIA COLI O157:H7 IN PACKAGED DRINKING-WATER IN ABEOKUTA, NIGERIA - Ajibola, Abiola; Shittu, Olufunke Biolatitio; Oluwasanya, Grace; Akinduti, Paul; Ojo, Abidemi; Akintokun, Aderonke (Polish Journal of Natural Sciences, 2023)
Many packaged sachet water (PSW) sold in Nigeria do not comply with drinking-water quality standards, therefore regular microbiological analysis of PSW is encouraged. One hundred and fifty three PSW samples from fifty one packaged sachet water facilities (PWMFs) in Abeokuta were collected from retail outlets between April - July, 2014. Samples were analyzed for Escherichia coli using standard culture media. Latex agglutination serological test; sequencing of 16S rRNA gene and sequence similarity analysis yielded E. coli O157: H7 from two PSW (1.32%) from one PWMF (1.96%). Both isolates were shiga toxin (stx1) positive but stx2 negative. The two strains exhibited different resistance patterns to ten (10) antibiotics belonging to seven (7) different classes. Each strain showed resistance to more than two classes of antibiotics with MIC ≥8 µg/ml. This paper showed that pathogenic, multidrug resistant and shiga, toxin-producing E. coli is disseminated through packaged sachet water in Nigeria.